Development formulation of crafts weaving batik ikat East Java: Strategic block and interconnection - Didiek Tranggono; Jojok Dwiridhotjahjono; Maria Indira Aryani; Resa Rasyidah (Universitas Hayam Wuruk Perbanas, 2015)
Batik tenun ikat has been the traditional legacy in some areas of East Java. This research is based on the findings and analysis on batik tenun ikat in Kediri and Lamongan. The data were collected from observation, in depth-interview, and printed documentations. The SWOT analysis showed that batik tenun ikat in Kediri and Lamongan got the position number two (2). Thus, the priority strategies are 1) extending partnership, 2) diversification of products and 3) e-marketing and integrated one-web destination. In applying those strategies the need of implementation of strategic block and interconnection is inevitable. Strategic blocs and interconnection would deeply increased the connectivity among the actors and hence between the economic elements.